LiPO2F2 as an Electrolyte Additive in Li[Ni0.5Mn0.3Co0.2]O2/Graphite Pouch Cells. Issue 5 (1st January 2018) - Ma, Lin; Ellis, Leah; Glazier, S. L.; Ma, Xiaowei; Liu, Qianqian; Li, Jing; Dahn, J. R.
Abstract : The effect of LiPO2 F2 as an electrolyte additive in Li[Ni0.5 Mn0.3 Co0.2 ]O2 (NMC532)/graphite pouch cells was examined using ultra high precision coulometry (UHPC), electrochemical impedance spectroscopy (EIS), storage testing, gas evolution measurements, isothermal calorimetry and long term charge-discharge cycling. Comparisons to the well-known additive, vinylene carbonate (VC) were made. LiPO2 F2 is an effective additive for NMC532/graphite pouch cells since it was found to improve coulombic efficiency, decrease parasitic heat flow, improve charge-discharge cycle lifetime and decrease impedance growth. The composition of the solid electrolyte interphases (SEI) on both electrodes was examined by X-ray photoelectron spectroscopy in cases where LiPO2 F2 was used or not used. The effect of combining methyl acetate, as a co-solvent to improve rate capability, and LiPO2 F2 was also investigated using long term cycling testing at 20°C. Overall, LiPO2 F2 is shown to be an extremely valuable electrolyte additive, more effective than VC in these cells.